Suitably Altering Amid Predicaments in Rural Nepal - Upadhyay, Prakash (Himalayan Journal of Sociology and Anthropology, 2014)
The major argument of this article is that societies and cultures are dynamic and triggered by various dynamics. However the past legacy of quandary affects the present societal development. To this zing, the rural communities in Bandipur who have been the victims of apathy and desertion in the past are more susceptible to quandary underneath the obsessive pressure of tourism and modernization at the present. This has created circumstances with a high probability of cultural conflict between tourists and locals, entrepreneurs and the commons. Nevertheless, local entrepreneurs involved in tourism business perceive tourism’s upshot more optimistically and sturdily in immediate sense than tourisms cultural consequences and insinuation in the long nudge. DOI: http://dx.doi.org/10.3126/hjsa.v6i0.10717 Himalayan Journal of Sociology and Anthropology Vol.6 2014: 187-202